Structural adhesive and preparation method thereof, photocuring structural adhesive, battery, battery pack and electric equipment
By introducing polyurethane resin, acrylic resin and R-based carbon material into the UV photocuring glue, a photocured structural glue with suitable energy storage modulus was prepared, which solved the problems of excessive energy storage modulus and insufficient vibration resistance of the existing UV photocuring glue, and achieved better mechanical support and thermal expansion stress buffering effects.
Patent Information
- Application Number
- CN202411441310.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-10-15
AI Technical Summary
The existing UV photocured adhesives face the problems of excessive energy storage modulus and insufficient vibration resistance, which limits their application in new energy vehicles and energy storage fields.
A combination of polyurethane resin, acrylic resin, R-based carbon material and photocuring initiator is used to prepare a photocuring structural adhesive with an appropriate energy storage modulus by light curing under ultraviolet light.
The photocured structural adhesive provides strong mechanical support at room temperature to prevent the battery module from displacement or deformation, and reduces the energy storage modulus when the temperature rises, which can better buffer thermal expansion stress and reduce the impact of temperature changes on the battery structure.
Smart Images

Figure CN119775945A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photocurable structural adhesives, and in particular to a structural adhesive and a preparation method thereof, a photocurable structural adhesive, a battery, a battery pack, and electrical equipment. Background Art
[0002] As one of the main materials for mass production of lithium-ion batteries, structural adhesive plays the role of reliably connecting and fixing the battery cell to the packaging shell. Therefore, its performance is one of the key factors affecting the safety, mechanical strength, structural stability and service life of the battery pack.
[0003] As one of the most commonly used structural adhesives, polyurethane glue has the advantages of high bonding strength and good flexibility, and can meet the connection requirements between battery cells and packaging shells. However, polyurethane glue has defects such as slow curing speed and sensitivity to air humidity, which limits its usage scenarios.
[0004] UV light-curing glue is a new type of glue with the characteristics of fast curing speed (10 to 20 seconds), high structural strength, and thin adhesive layer thickness. It is particularly suitable for application scenarios that require fast curing. However, existing UV light-curing glue faces the problems of too high storage modulus and insufficient vibration resistance. Summary of the invention
[0005] The invention provides a structural adhesive which can be rapidly polymerized and cured under ultraviolet light to obtain a light-cured structural adhesive with a suitable storage modulus.
[0006] The present invention also provides a method for preparing the structural adhesive. The method is simple to operate and can successfully prepare the structural adhesive.
[0007] The present invention also provides a photocurable structural adhesive, which is obtained by photocuring the above structural adhesive under ultraviolet light. The photocurable structural adhesive has a relatively suitable storage modulus, can provide strong mechanical support at room temperature, and prevent the battery assembly from displacement or deformation during use. As the temperature rises, the storage modulus of the photocurable structural adhesive decreases relatively, which can better buffer thermal expansion stress and reduce the impact of temperature changes on the battery structure.
[0008] In a first aspect, the present invention provides a structural adhesive, comprising: a polyurethane resin, an acrylic resin, an R-group-containing carbon material, and a photocuring initiator, wherein the R group is used to chemically connect with at least one of the polyurethane resin and the acrylic resin, and the carbon material is a one-dimensional and / or two-dimensional carbon material;
[0009] The total mass of the polyurethane resin and the acrylic resin is n, and the mass of the R-group-containing carbon material is m, wherein n and m satisfy: 0.01%≤m / n×100%≤0.5%.
[0010] Furthermore, the polymerization degree of the polyurethane resin is 10-100; the polymerization degree of the acrylic resin is 10-100.
[0011] Furthermore, the polymerization degree of the polyurethane resin is 30-50; the polymerization degree of the acrylic resin is 30-50.
[0012] Furthermore, the R group is modified on at least a portion of the surface of the carbon material, and the R group includes at least one of a hydroxyl group, a carboxyl group, and a thiol group.
[0013] Furthermore, the carbon material has an oxygen content of 1% to 10% by mass.
[0014] Furthermore, the carbon material includes graphene containing the R group and carbon nanotubes containing the R group.
[0015] Furthermore, the mass ratio of the graphene containing R groups to the carbon tube containing R groups is 1:3-7, and / or the aspect ratio of the carbon nanotube is 10 3 -10 6 .
[0016] Furthermore, the mass ratio of the acrylic resin to the polyurethane resin is 1-2:1-2, preferably 1:1.005-1.1;
[0017] and / or, the carbon material accounts for 0.01% to 0.5% of the total mass of the polyurethane resin and the acrylic resin;
[0018] And / or, the photocuring initiator accounts for 0.1% to 0.5% of the total mass of the polyurethane resin and the acrylic resin.
[0019] In a second aspect, the present invention provides a method for preparing the structural adhesive according to the first aspect, comprising the following steps:
[0020] The acrylic acid ester monomer is polymerized into a polyacrylate resin under the action of a first initiator, and the acrylic acid resin is obtained after acid treatment;
[0021] Diisocyanate or its derivative and polyol are polymerized into the polyurethane resin under the action of a second initiator;
[0022] The acrylic resin, the polyurethane resin and the carbon material are mixed, and a photocuring initiator is added to obtain the structural adhesive.
[0023] In a third aspect, the present invention provides a photocurable structural adhesive obtained by photocuring the structural adhesive described in the first aspect under ultraviolet light.
[0024] In a fourth aspect, the present invention provides a battery comprising the photocurable adhesive described in the second aspect.
[0025] In a fifth aspect, the present invention provides a battery pack comprising the battery described in the fourth aspect.
[0026] In a sixth aspect, the present invention provides an electrical device comprising the battery described in the fourth aspect or the battery pack described in the fifth aspect.
[0027] The structural adhesive provided by the invention can be rapidly polymerized and cured under ultraviolet light to obtain a light-cured structural adhesive with a suitable elastic modulus.
[0028] Furthermore, the photocurable structural adhesive provided by the present invention has a relatively suitable storage modulus, which can provide strong mechanical support at room temperature to prevent the battery components from being displaced or deformed during use. As the temperature rises, the storage modulus of the photocurable structural adhesive decreases relatively, which can better buffer the thermal expansion stress, thereby reducing the impact of temperature changes on the battery structure. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.
[0030] Figure 1 This is a comparison diagram of the storage modulus of the light-curing structural adhesives of Example 1, Example 2, and Example 3 at different temperatures;
[0031] Figure 2 The storage modulus diagram of the light-curing structural adhesive of Example 4 at different temperatures;
[0032] Figure 3 This is a storage modulus diagram of the light-curing structural adhesive of Example 5 at different temperatures;
[0033] Figure 4 This is a diagram of the storage modulus of the photocurable structural adhesive of comparative example 1 at different temperatures. DETAILED DESCRIPTION
[0034] In order to enable those skilled in the art to better understand the scheme of the present invention, the present invention is further described in detail below. The specific implementation methods listed below are only for describing the principles and features of the present invention. The examples are only used to explain the present invention and are not intended to limit the scope of the present invention. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0035] UV light-curing adhesive has the advantages of high strength and wide adaptability to substrates, but when used in the field of new energy vehicles and energy storage, it faces the problems of high brittleness and insufficient elasticity. These shortcomings seriously limit its application in the field of new energy vehicles and energy storage. Therefore, it is necessary to provide a light-curable structural adhesive with a suitable storage modulus. To this end, the present invention provides the following technical solutions:
[0036] In a first aspect, the present invention provides a structural adhesive, comprising: a polyurethane resin, an acrylic resin, an R-group-containing carbon material, and a photocuring initiator, wherein the R group is used to chemically connect with at least one of the polyurethane resin and the acrylic resin, and the carbon material is a one-dimensional and / or two-dimensional carbon material;
[0037] The total mass of the polyurethane resin and the acrylic resin is n, and the mass of the R-group-containing carbon material is m, wherein n and m satisfy: 0.01%≤m / n×100%≤0.5%.
[0038] It should be noted that the chemical connection refers to the combination of the R group and at least one of the polyurethane resin and the acrylic resin through a chemical bond.
[0039] The structural adhesive of the present invention can be rapidly polymerized and cured under ultraviolet light, and a photocurable structural adhesive with a suitable elastic modulus is obtained, which provides a more solid bonding, sealing, fixing and elastic protection function for the battery unit. In detail, the structural adhesive of the present invention introduces polyurethane resin and acrylic resin to make it have good weather resistance, chemical resistance, good flexibility and elongation after curing, and the one-dimensional and / or two-dimensional carbon material containing R group can be chemically connected with polyurethane resin and acrylic resin, and the movement of polymer chain is restricted at room temperature, so that the photocurable structural adhesive exhibits a higher elastic energy storage capacity, significantly improving the tensile strength and compressive strength of the colloid, and as the temperature rises, the polymer chain formed by polyurethane resin and acrylic resin moves faster, the restrictive effect of carbon material on polymer chain is relatively reduced, and the storage modulus of photocurable structural adhesive is reduced, so as to better buffer thermal expansion stress, thereby reducing the influence of temperature change on battery structure. Moreover, the carbon material of the above-mentioned one-dimensional and / or two-dimensional material has a high specific surface area, which helps to disperse stress and reduce the propagation of cracks, thereby improving the fracture toughness of the structural adhesive.
[0040] The photocuring initiator is not particularly limited in the present invention, and can be, for example, selected from one or more of 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2,2-dimethoxy-2-phenylacetophenone, 2-methyl-[4-(methylthio)phenyl]-2-morpholinylpropane-1-one, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinyl-1-propanone, benzoin ethyl ether, diphenyliodonium hexafluorophosphate, diphenylsulfonium hexafluorophosphate, and triphenyliodonium hexafluoroantimonate.
[0041] In some embodiments, m / n×100%=0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, etc.
[0042] In some embodiments, the polymerization degree of the polyurethane resin is 10-100; the polymerization degree of the acrylic resin is 10-100.
[0043] Among them, since the polyurethane resin and acrylic resin in the above-mentioned embodiment have a certain degree of polymerization, the structural adhesive composed of them has a certain viscosity and is easier to process and coat. In addition, the above-mentioned polyurethane resin and acrylic resin with a certain degree of polymerization and carbon material can form a certain chemical connection, which is conducive to the formation of a photocurable structural adhesive with a higher elastic modulus after curing.
[0044] In a specific embodiment, the polymerization degree of the polyurethane resin is 30-50; the polymerization degree of the acrylic resin is 30-50.
[0045] Illustratively, the polymerization degree of the polyurethane resin is any value among 30, 32, 35, 37, 40, 42, 45, 47, etc., and the polymerization degree of the acrylic resin is any value among 30, 32, 35, 37, 40, 42, 45, 47, etc.
[0046] In some embodiments, the R group is modified on at least part of the surface of the carbon material, and the R group includes at least one of a hydroxyl group, a carboxyl group, and a thiol group. Among them, the carbon material containing at least one of a hydroxyl group (-OH), a carboxyl group (-COOH), and a thiol group (-SH) is more likely to form a chemical bond with a polyurethane resin and / or an acrylic resin, thereby effectively limiting the movement of the polymer chain formed by the polyurethane resin and the acrylic resin at a higher temperature, and avoiding excessive reduction in the storage modulus of the photocurable structural adhesive.
[0047] The above R-group modified carbon material can be directly purchased from the market, or can be prepared by existing means. For example, the hydroxyl-modified carbon material can be prepared by the following process:
[0048] The carbon material is mixed with a strong oxidant (such as potassium permanganate, nitric acid, hydrogen peroxide, etc.), stirred at room temperature for 1-21 hours, and then filtered, washed and dried to obtain a hydroxyl-modified carbon material.
[0049] In order to further strengthen the chemical connection strength between the carbon material and the polyurethane resin and / or acrylic resin, in some embodiments, the oxygen content of the carbon material is 1% to 10% by mass. The oxygen content of the carbon material can reflect the content of hydroxyl groups, carboxyl groups, etc. The carbon material of this embodiment helps to improve the storage modulus of the light-cured structural adhesive.
[0050] Exemplarily, the oxygen content of the carbon material is any value of 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, etc., and the oxygen content of the carbon material can be obtained by testing with an oxygen, nitrogen and hydrogen analyzer.
[0051] In some embodiments, the carbon material includes graphene containing the R group and carbon nanotube containing the R group.
[0052] In the above-mentioned embodiments, the carbon material includes two-dimensional graphene and one-dimensional carbon nanotubes, which helps to further maintain a more suitable storage modulus of the photocurable structural adhesive because it can more effectively restrict the movement of polymer chains than single-dimensional carbon materials. In addition, the high-aspect-ratio carbon nanotubes and flaky graphene compound can also improve the thermal conductivity of the structural adhesive and help dissipate heat, especially in high-power density battery applications, which helps to extend battery life and improve safety.
[0053] In some embodiments, the mass ratio of the graphene containing R groups to the carbon nanotube containing R groups is 1:3-7, and / or the aspect ratio of the carbon nanotube is 10 3 -10 6 .
[0054] The specific size of the graphene is not particularly limited in the present invention. For example, the lateral size of the graphene is 2nm-10μm, further 10nm-7μm, further 1μm-5μm, and the thickness of the graphene is 0.5nm-20nm, further 0.5nm-10nm, further 2nm-5nm. The specific size of the carbon nanotube is also not particularly limited in the present invention. For example, the diameter of the carbon nanotube is 2nm-20nm, further 1nm-15nm, further 5nm-10nm.
[0055] In some embodiments, the mass ratio of the acrylic resin to the polyurethane resin is 1-2:1-2, preferably 1:1.005-1.1; the ratio of the acrylic resin to the polyurethane resin is within the above range, which can better balance the weather resistance, chemical resistance, flexibility and elongation of the photocurable structural adhesive.
[0056] Among them, although the introduction of carbon materials is helpful to the storage modulus of the photocurable structural adhesive, too much carbon material will increase the loss modulus of the photocurable structural adhesive and reduce the compressive resistance. Therefore, in order to avoid the increase of the loss modulus of the photocurable structural adhesive, in some embodiments, the carbon material accounts for 0.01%-0.5% of the total mass of the polyurethane resin and the acrylic resin.
[0057] In some embodiments, the photocuring initiator accounts for 0.1% to 0.5% of the total mass of the polyurethane resin and the acrylic resin.
[0058] In a second aspect, the present invention provides a method for preparing the structural adhesive according to the first aspect, comprising the following steps:
[0059] The acrylic acid ester monomer is polymerized into a polyacrylate resin under the action of a first initiator, and the acrylic acid resin is obtained after acid treatment;
[0060] Diisocyanate or its derivative and polyol are polymerized into the polyurethane resin under the action of a second initiator;
[0061] The acrylic resin, the polyurethane resin and the carbon material are mixed, and a photocuring initiator is added to obtain the structural adhesive.
[0062] Exemplarily, the above-mentioned acrylate monomers include but are not limited to: one or more of acrylic acid monomer, ethyl acrylate, butyl acrylate, hydroxyethyl acrylate, dodecyl acrylate, isooctyl acrylate; the first initiator includes but is not limited to: one or more of BPO, di-tert-butyl peroxide, AIBN, ADPA; the addition amount of the first initiator is 0.02% to 0.08% of the mass of the acrylate monomer; the acidic substance used includes but is not limited to one or more of acetic acid, oxalic acid, succinic acid, tartaric acid, fumaric acid, and salicylic acid;
[0063] Exemplarily, the above-mentioned diisocyanate includes but is not limited to: one or more of hexamethylene diisocyanate, toluene diisocyanate, naphthyl diisocyanate, and cyclohexane diisocyanate; the polyol includes but is not limited to: one or more of ethylene glycol, propylene glycol, pentaerythritol, and trimethylolpropane; the second initiator includes but is not limited to: one or more of triethylamine, dimethylcyclohexylamine, and octanoic acid dimethylamine, and the addition amount of the second initiator is 0.01% to 0.05% of the mass of the diisocyanate;
[0064] In a specific embodiment, the preparation of the above structural adhesive is carried out in a reaction vessel, and the reaction vessel includes a glass reactor, an enamel reactor, a PP / PE lined stainless steel reactor, a 316L stainless steel reactor, etc.
[0065] In a specific implementation, the steps are specifically included:
[0066] 1) Add the first initiator to the acrylic acid ester monomer at a fixed rate of 1 g / min at 50-70° C., and maintain the temperature for a single polymerization for 10-60 minutes;
[0067] 2) Add polyol to the system at a fixed rate of 0.5 L / min, stir at 50-70°C for 1h-3h, add the second initiator to the system at a fixed rate of 1g / min, and continue heating and stirring for 10min-60min;
[0068] 3) Mix acrylate oligomer X and polyurethane resin oligomer Y, add functionalized carbon material in N times, N is greater than 1, add photocuring initiator at 50-70° C., and continue heating and stirring for 10-60 minutes.
[0069] In a third aspect, the present invention provides a photocurable structural adhesive obtained by photocuring the structural adhesive described in the first aspect under ultraviolet light.
[0070] The source of the ultraviolet light is not particularly limited in the present invention. In some embodiments, it may be a 254nm mercury lamp, a xenon lamp, a UV LED, a UV laser, a black light lamp, a cold cathode fluorescent lamp, etc.
[0071] In a fourth aspect, the present invention provides a battery comprising the photocurable adhesive described in the second aspect.
[0072] In a fifth aspect, the present invention provides a battery pack comprising the battery described in the fourth aspect.
[0073] In a sixth aspect, the present invention provides an electrical device comprising the battery described in the fourth aspect or the battery pack described in the fifth aspect.
[0074] The present invention does not limit the specific types of electrical equipment, and may include electric vehicles, mobile phones, smart homes, robots, drones, electronic cigarettes, speakers, and any other equipment that requires batteries to power them.
[0075] The present invention is further described below in conjunction with specific embodiments:
[0076] Among them, the dynamic thermomechanical analysis (DMA) test method involved in the following tests refers to: GBT40396-2021.
[0077] Example 1
[0078] This example provides a structural adhesive and a photocurable structural adhesive, the structural adhesive comprising: a polyurethane resin, an acrylic resin, a carbon material containing an R group and a photocurable initiator, wherein the R group is a hydroxyl group and a carboxyl group;
[0079] The polymerization degree of the polyurethane resin is 30-50, the polymerization degree of the acrylic resin is 30-50, and the mass ratio of the polyurethane resin to the acrylic resin is 1:1.005; the carbon material is graphene containing hydroxyl and carboxyl groups and carbon nanotubes containing hydroxyl and carboxyl groups, and the photocuring initiator is 2-hydroxy-2-methyl-1-phenyl-1-propanone; the total mass of the polyurethane resin and the acrylic resin is 100%, wherein the graphene accounts for 0.01%, the carbon nanotubes account for 0.01%, and the photocuring initiator accounts for 0.1%; the oxygen content of the carbon material is about 1%, the diameter of the carbon nanotubes is 2nm, and the aspect ratio is 10 3 -10 6 , the size of graphene is 3μm.
[0080] The method for preparing a structural adhesive comprises the following steps:
[0081] 1) Ethyl acrylate is put into an enamel reactor, heated to 50° C. and stirred for 60 minutes, and 0.02% of the monomer mass of dibenzoyl peroxide (BPO) is added to the system at a fixed rate of 1 g / min, and heated and stirred for 10 minutes to obtain an intermediate product; oxalic acid is added to the reactor to adjust the pH to 5, and heated and stirred for 30 minutes to obtain acrylic resin oligomer Y; heating is stopped, and the mixture is cooled to room temperature with stirring.
[0082] 2) Hexamethylene diisocyanate was added into an enameled reactor, heated to 50°C and stirred for 60 minutes, ethylene glycol was added into the system at a fixed rate of 0.5 L / min, and the stirring and heating were continued for 60 minutes. After that, triethylamine accounting for 0.01% of the monomer mass was added into the system at a fixed rate of 1 g / min, and the heating and stirring were continued for 10 minutes to obtain a polyurethane resin oligomer Z.
[0083] 3) The acrylic resin oligomer Y and the polyurethane resin oligomer Z are stirred and mixed at a fixed ratio of 1:1.005, and the mixture of graphene dry powder and carbon nanotubes is added three times during the mixture. After stirring evenly, 2-hydroxy-2-methyl-1-phenyl-1-propanone is added and stirred for 10 minutes to obtain a structural adhesive.
[0084] The above-mentioned light-curing structural adhesive is obtained by curing the structural adhesive with an ultraviolet lamp, and a standard sample with a size of 1mm×2mm×20mm is obtained for dynamic mechanical analysis (DMA) test. Figure 1 The material storage modulus trend graph is shown.
[0085] Example 2
[0086] This example provides a structural adhesive and a photocurable structural adhesive, the structural adhesive comprising: a polyurethane resin, an acrylic resin, a carbon material containing an R group and a photocurable initiator, wherein the R group is a hydroxyl group and a mercapto group;
[0087] The polymerization degree of the polyurethane resin is 30-50, the polymerization degree of the acrylic resin is 30-50, and the mass ratio of the polyurethane resin to the acrylic resin is 1:1.005; the carbon material is graphene containing hydroxyl and thiol groups and carbon nanotubes containing hydroxyl and thiol groups, and the photocuring initiator is 2-hydroxy-2-methyl-1-phenyl-1-propanone; the total mass of the polyurethane resin and the acrylic resin is 100%, graphene accounts for 0.01%, carbon nanotubes account for 0.01%, and photocuring initiator accounts for 0.1%; the oxygen content of the carbon material is about 1.5%, the diameter of the carbon nanotubes is 1nm, and the aspect ratio is 10 3 -10 6 , the size of graphene is 5μm.
[0088] The method for preparing a structural adhesive comprises the following steps:
[0089] 1) Ethyl acrylate was added into an enamel reactor, heated to 60°C and stirred for 70 minutes, 0.03% BPO was added to the system at a fixed rate of 1 g / min, and the mixture was heated and stirred for 20 minutes to obtain an intermediate product. Oxalic acid was added into the reactor to adjust the pH to 5, and the mixture was heated and stirred for 40 minutes to obtain an acrylic resin oligomer Y. The heating was stopped, and the mixture was cooled to room temperature with stirring.
[0090] 2) Hexamethylene diisocyanate was added into an enameled reactor, heated to 60°C and stirred for 70 minutes, ethylene glycol was added into the system at a fixed rate of 0.5 L / min, and the heating and stirring were continued for 70 minutes. After adding triethylamine accounting for 0.02% of the monomer mass into the system at a fixed rate of 1 g / min, the heating and stirring were continued for 20 minutes to obtain a polyurethane resin oligomer Z.
[0091] 3) The acrylic resin oligomer Y and the polyurethane resin oligomer Z are stirred and mixed at a fixed ratio of 1:1.005, during which 0.01% of the functionalized graphene dry powder and 0.01% of the functionalized carbon nanotube mixture based on the total mass of the polymer are added three times, and after stirring evenly, 0.1% of 2-hydroxy-2-methyl-1-phenyl-1-propanone is added, and stirred for 10 minutes to obtain a structural adhesive.
[0092] The above-mentioned light-cured structural adhesive is obtained by curing the structural adhesive with an ultraviolet lamp, and a standard sample with a size of 1mm×2mm×20mm is obtained for DMA test. The slurry material is finally obtained as follows Figure 1 The material storage modulus trend graph is shown.
[0093] Example 3
[0094] This example provides a structural adhesive and a photocurable structural adhesive, the structural adhesive comprising: a polyurethane resin, an acrylic resin, a carbon material containing an R group and a photocurable initiator, wherein the R group is a hydroxyl group and a carboxyl group;
[0095] The polymerization degree of the polyurethane resin is 30-50, the polymerization degree of the acrylic resin is 30-50, and the mass ratio of the polyurethane resin to the acrylic resin is 1:1.005; the carbon material is hydroxyl and carboxyl graphene and hydroxyl and carboxyl carbon nanotubes, and the photocuring initiator is 2-hydroxy-2-methyl-1-phenyl-1-propanone; the total mass of the polyurethane resin and the acrylic resin is 100%, the graphene accounts for 0.01%, the carbon nanotube accounts for 0.01%, and the photocuring initiator accounts for 0.1%; the oxygen content of the carbon material is about 2%, the diameter of the carbon nanotube is 0.5nm, and the aspect ratio is 10 3 -10 6 , the size of graphene is 7μm.
[0096] The method for preparing a structural adhesive comprises the following steps:
[0097] 1) Ethyl acrylate is put into an enameled reactor, heated to 70° C. and stirred for 80 minutes, BPO accounting for 0.03% of the monomer mass is added into the system at a fixed rate of 1 g / min, and heating and stirring are continued for 40 minutes to obtain an intermediate product, oxalic acid is added into the reactor to adjust the pH to 5, heating and stirring are continued for 50 minutes to obtain an acrylic resin oligomer Y, and heating is stopped, and the mixture is cooled to room temperature with stirring.
[0098] 2) Hexamethylene diisocyanate was added into an enameled reactor, heated to 70°C and stirred for 80 minutes, ethylene glycol was added into the system at a fixed rate of 0.5 L / min, and the stirring and heating were continued for 80 minutes. After adding triethylamine accounting for 0.02% of the monomer mass into the system at a fixed rate of 1 g / min, the heating and stirring were continued for 40 minutes to obtain a polyurethane resin oligomer Z.
[0099] 3) The acrylic resin oligomer Y and the polyurethane resin oligomer Z are stirred and mixed at a fixed ratio of 1:1.01, and 0.01% of the functionalized graphene dry powder and 0.01% of the functionalized carbon nanotube mixture based on the total mass of the polymer are added three times. After stirring evenly, 2-hydroxy-2-methyl-1-phenyl-1-propanone is added and stirred for 10 minutes to obtain a structural adhesive.
[0100] The above-mentioned light-cured structural adhesive is obtained by curing the structural adhesive with an ultraviolet lamp, and a standard sample with a size of 1mm×2mm×20mm is obtained for DMA test. The slurry material is finally obtained as follows Figure 1 The material storage modulus trend graph is shown.
[0101] Example 4
[0102] This example provides a structural adhesive and a photocurable structural adhesive, the structural adhesive comprising: a polyurethane resin, an acrylic resin, a carbon material containing an R group and a photocurable initiator, wherein the R group is a carboxyl group;
[0103] The polymerization degree of the polyurethane resin is 30-50, the polymerization degree of the acrylic resin is 30-50, and the mass ratio of the polyurethane resin to the acrylic resin is 1:1.1; the carbon material is carboxyl-containing graphene and carboxyl-containing carbon nanotubes, and the photocuring initiator is 2-hydroxy-2-methyl-1-phenyl-1-propanone; the total mass of the polyurethane resin and the acrylic resin is 100%, graphene accounts for 0.1%, carbon nanotubes account for 0.3%, and photocuring initiator accounts for 0.1%; the oxygen content of the carbon material is about 2.5%, the diameter of the carbon nanotubes is 0.3nm, and the aspect ratio is 10 3 -10 6 , the size of graphene is 10μm.
[0104] The method for preparing a structural adhesive comprises the following steps:
[0105] 1) Ethyl acrylate and hydroxyethyl acrylate in a ratio of 1:1 were added into an enamel reactor, heated to 70°C and stirred for 120 minutes, and AIBN accounting for 0.04% of the monomer mass was added into the system at a fixed rate of 1 g / min. After continuous heating and stirring for 60 minutes, an intermediate product was obtained. Oxalic acid was added into the reactor to adjust the pH to 5, and heating and stirring were continued for 100 minutes to obtain acrylic resin oligomer Y. Heating was stopped, and the mixture was stirred and cooled to room temperature.
[0106] 2) Toluene diisocyanate was added into an enameled reactor, heated to 70°C and stirred for 180 minutes, pentaerythritol was added into the system at a fixed rate of 0.5 L / min, and the stirring and heating were continued for 120 minutes. After tetramethylpropylenediamine accounting for 0.02% of the monomer mass was added into the system at a fixed rate of 1 g / min, the heating and stirring were continued for 60 minutes to obtain a polyurethane resin oligomer Z.
[0107] 3) The acrylic resin oligomer Y and the polyurethane resin oligomer Z are stirred and mixed at a fixed ratio of 1:1.1, and 0.1% of the functionalized graphene dry powder and 0.3% of the functionalized carbon nanotube mixture based on the total mass of the polymer are added three times. After stirring evenly, 0.2% of 2-hydroxy-2-methyl-1-phenyl-1-propanone is added, and the mixture is stirred for 10 minutes to obtain a structural adhesive.
[0108] The above-mentioned light-cured structural adhesive is obtained by curing the structural adhesive with an ultraviolet lamp, and a standard sample with a size of 1mm×2mm×20mm is obtained for DMA test. The slurry material is finally obtained as follows Figure 2 The material storage modulus trend graph is shown.
[0109] Example 5
[0110] This example provides a structural adhesive and a photocurable structural adhesive, the structural adhesive comprising: a polyurethane resin, an acrylic resin, a carbon material containing an R group and a photocurable initiator, wherein the R group is a hydroxyl group;
[0111] The polymerization degree of the polyurethane resin is 30-50, the polymerization degree of the acrylic resin is 30-50, and the mass ratio of the polyurethane resin to the acrylic resin is 1:1.1; the carbon material is hydroxyl-containing graphene and hydroxyl carbon nanotubes, and the photocuring initiator is 2-hydroxy-2-methyl-1-phenyl-1-propanone; the total mass of the polyurethane resin and the acrylic resin is 100%, the graphene accounts for 0.1%, the carbon nanotubes account for 0.4%, and the photocuring initiator accounts for 0.1%; the oxygen content of the carbon material is about 3%, the diameter of the carbon nanotubes is 1nm, and the aspect ratio is 10 3 -10 6 , the size of graphene is 3μm.
[0112] The method for preparing a structural adhesive comprises the following steps:
[0113] 1) Ethyl acrylate and hydroxyethyl acrylate in a ratio of 1:1 were added into an enamel reactor, heated to 70°C and stirred for 120 minutes, and AIBN accounting for 0.2% of the monomer mass was added into the system at a fixed rate of 1 g / min. After heating and stirring for 60 minutes, an intermediate product was obtained. Tartaric acid was added into the reactor to adjust the pH to 5, and heating and stirring were continued for 100 minutes to obtain acrylic resin oligomer Y. Heating was stopped, and the mixture was stirred and cooled to room temperature.
[0114] 2) Toluene diisocyanate was added into an enameled reactor, and the reaction mixture was continuously heated to 70° C. and stirred for 180 minutes. Pentaerythritol was added into the system at a fixed rate of 0.5 L / min, and the heating was continuously stirred for 120 minutes. Tetramethylpropylenediamine accounting for 0.03% of the monomer mass was added into the system at a fixed rate of 1 g / min, and the reaction mixture was continuously heated and stirred for 60 minutes to obtain a polyurethane resin oligomer Z.
[0115] 3) The acrylic resin oligomer Y and the polyurethane resin oligomer Z are stirred and mixed at a fixed ratio of 1:1.1, and 0.1% of the functionalized graphene dry powder and 0.4% of the functionalized carbon nanotube mixture based on the total mass of the polymer are added three times. After stirring evenly, 0.2% of 1-hydroxycyclohexyl phenyl ketone is added and stirred for 10 minutes to obtain a structural adhesive.
[0116] The above-mentioned light-cured structural adhesive is obtained by curing the structural adhesive with an ultraviolet lamp, and a standard sample with a size of 1mm×2mm×20mm is obtained for DMA test. The slurry material is finally obtained as follows Figure 3 The material storage modulus trend graph is shown.
[0117] Comparative Example 1
[0118] This example provides a structural adhesive and a photocurable structural adhesive, the structural adhesive comprising: a polyurethane resin, an acrylic resin, a carbon material containing an R group and a photocurable initiator, wherein the R group is a hydroxyl group and a carboxyl group;
[0119] The polymerization degree of the polyurethane resin is 30-50, the polymerization degree of the acrylic resin is 30-50, and the mass ratio of the polyurethane resin to the acrylic resin is 1:1.1; the carbon material is graphene containing hydroxyl and carboxyl groups and carbon nanotubes containing hydroxyl and carboxyl groups, and the photocuring initiator is 2-hydroxy-2-methyl-1-phenyl-1-propanone; the total mass of the polyurethane resin and the acrylic resin is 100%, graphene accounts for 0.3%, carbon nanotubes account for 0.5%, and photocuring initiator accounts for 0.1%; the oxygen content of the carbon material is about 1%, the diameter of the carbon nanotubes is 1nm, and the aspect ratio is 10 3 -10 6 , the size of graphene is 3μm.
[0120] The method for preparing a structural adhesive comprises the following steps:
[0121] 1) Ethyl acrylate and hydroxyethyl acrylate in a ratio of 1:1 were added into an enamel reactor, heated to 70°C and stirred for 120 minutes, and AIBN accounting for 0.3% of the monomer mass was added into the system at a fixed rate of 1 g / min. After heating and stirring for 60 minutes, an intermediate product was obtained. Tartaric acid was added into the reactor to adjust the pH to 5, and heating and stirring were continued for 100 minutes to obtain acrylic resin oligomer Y. Heating was stopped, and the mixture was cooled to room temperature with stirring.
[0122] 2) Toluene diisocyanate was added into an enameled reactor, heated to 70°C and stirred for 180 minutes, pentaerythritol was added into the system at a fixed rate of 0.5 L / min, and the heating was continued with stirring for 120 minutes, and tetramethylpropylenediamine accounting for 0.3% of the monomer mass was added into the system at a fixed rate of 1 g / min, and the heating and stirring were continued for 60 minutes to obtain a polyurethane resin oligomer Z.
[0123] 3) The acrylic resin oligomer Y and the polyurethane resin oligomer Z are stirred and mixed at a fixed ratio of 1:1.1, during which 0.3% of the functionalized graphene dry powder and 0.5% of the functionalized nanocarbon tube mixture based on the total mass of the polymer are added three times, and after stirring evenly, 0.2% of 1-hydroxycyclohexyl phenyl ketone is added, and stirred for 60 minutes to obtain a structural adhesive.
[0124] The above-mentioned light-cured structural adhesive is obtained by curing the structural adhesive with an ultraviolet lamp, and a standard sample with a size of 1mm×2mm×20mm is obtained for DMA test. The slurry material is finally obtained as follows Figure 4 The material storage modulus trend graph is shown.
[0125] By comparison Figure 1-4 It can be seen that: compared with the comparative example, the storage modulus of the photocurable structural adhesive of the embodiment is lower at room temperature, and as the temperature increases, the storage modulus decreases more significantly.
[0126] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A structural adhesive, characterized in that: include: A polyurethane resin, an acrylic resin, an R-group-containing carbon material and a photocuring initiator, wherein the R group is used to chemically connect with at least one of the polyurethane resin and the acrylic resin, and the carbon material is a one-dimensional and / or two-dimensional carbon material; The total mass of the polyurethane resin and the acrylic resin is n, and the mass of the R-group-containing carbon material is m, wherein n and m satisfy: 0.01%≤m / n×100%≤0.5%.
2. The structural adhesive according to claim 1, characterized in that: The polymerization degree of the polyurethane resin is 10-100; the polymerization degree of the acrylic resin is 10-100.
3. The structural adhesive according to claim 2, characterized in that: The polymerization degree of the polyurethane resin is 30-50; the polymerization degree of the acrylic resin is 30-50.
4. The structural adhesive according to any one of claims 1 to 3, characterized in that: The R group is modified on at least a portion of the surface of the carbon material, and the R group includes at least one of a hydroxyl group, a carboxyl group, and a thiol group.
5. The structural adhesive according to claim 4, characterized in that: The carbon material has an oxygen content of 1% to 10% by mass.
6. The structural adhesive according to any one of claims 1 to 5, characterized in that: The carbon material includes graphene containing the R group and carbon nanotube containing the R group.
7. The structural adhesive according to claim 6, characterized in that: The mass ratio of the graphene containing R groups and the carbon tube containing R groups is 1:3-7, and / or the aspect ratio of the carbon nanotube is 10 3 -10 6 .
8. The structural adhesive according to any one of claims 1 to 7, characterized in that: The mass ratio of the acrylic resin to the polyurethane resin is 1-2:1-2, preferably 1:1.005-1.1; and / or, the carbon material accounts for 0.01% to 0.5% of the total mass of the polyurethane resin and the acrylic resin; And / or, the photocuring initiator accounts for 0.1% to 0.5% of the total mass of the polyurethane resin and the acrylic resin.
9. A method for preparing a structural adhesive as claimed in any one of claims 1 to 8, characterized in that: The following steps are involved: The acrylic acid ester monomer is polymerized into a polyacrylate resin under the action of a first initiator, and the acrylic acid resin is obtained after acid treatment; Diisocyanate or its derivative and polyol are polymerized into the polyurethane resin under the action of a second initiator; The acrylic resin, the polyurethane resin and the carbon material are mixed, and a photocuring initiator is added to obtain the structural adhesive.
10. A photocurable structural adhesive obtained by photocuring the structural adhesive according to any one of claims 1 to 9 under ultraviolet light.
11. A battery, characterized in that: Contains the photocurable structural adhesive as described in claim 10.
12. A battery pack, characterized in that: A battery comprising the battery of claim 11.
13. An electrical equipment, characterized in that: Comprising the battery according to claim 11 or the battery pack according to claim 12.
Citation Information
Patent Citations
Aqueous photo-curing polyurethane resin and preparation thereof
CN101372530A
Ultraviolet-curing structural adhesive composition and application thereof
CN113512365A
High-flexibility UV light-cured acrylic acid structural adhesive for new energy battery and preparation method of high-flexibility UV light-cured acrylic acid structural adhesive
CN117004329A
Silicon-based ceramic core based on photocuring 3D printing and preparation method thereof
CN118724572A
Eco-friendly plastic sheet and its manufacturing method
KR102545549B1